2016
DOI: 10.1021/acs.jpcc.6b06876
|View full text |Cite
|
Sign up to set email alerts
|

CO Oxidation on the Au15Cu15 Cluster and the Role of Vacancies in the MgO(100) Support

Abstract: A comprehensive theoretical study of a Au 15 Cu 15 cluster on MgO(100) supports and its catalytic activity for CO oxidation has been performed based on the density functional theory and microkinetic modeling. Molecular adsorption and different reaction paths based on the Langmuir−Hinshelwood (LH) and Eley−Rideal (ER) mechanisms have been explored by tuning the location of vacancies in MgO(100). The charge states of the Au 15 Cu 15 cluster are negative on all supports, defect-free, O-vacancy (F-center), and Mg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 61 publications
(123 reference statements)
1
27
0
Order By: Relevance
“…For Au 15 Cu 15 supported on MgO, F-centers again facilitate CO oxidation, whereas Mg vacancies (V-centers) reduce the charge transfer to the cluster and harm the activity. However, the V-centers provide the strongest binding to the surface, making sintering less likely (93).…”
Section: Electronic Metal-support Interactionmentioning
confidence: 99%
“…For Au 15 Cu 15 supported on MgO, F-centers again facilitate CO oxidation, whereas Mg vacancies (V-centers) reduce the charge transfer to the cluster and harm the activity. However, the V-centers provide the strongest binding to the surface, making sintering less likely (93).…”
Section: Electronic Metal-support Interactionmentioning
confidence: 99%
“…The inherent stability exhibited by ligand protected NCs, along with their high surface-to-volume ratio, their precisely known surface structure, and discrete electronic states have made these NCs attractive functional materials for applications in catalysis [12][13][14][15][16][17][18][19][20][21][22][23][24][25], with the Au 25 NC being the most investigated NC for this purpose. Experimental and computational studies have demonstrated that the Au 25 NC exhibits exceptional catalytic behavior for the oxidation of styrene, CO, the hydrogenation of ketones and aldehydes, photocatalytic water splitting, and more recently, the electrochemical reduction of CO 2 [14,16,18,[20][21][22][25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Mozer et al [49] reported that high copper content in AuCu clusters can block the Au active sites, thus Cu-deficient clusters have increased catalytic activity for CO oxidation. Research of Ma and co-workers [8,50] on AuCu clusters on MgO showed that Au15Cu15 on MgO(100) has high activity for the dissociation of O2.…”
Section: Introductionmentioning
confidence: 99%
“…Studying sub-nanometre AuCu clusters, where quantum effects are observed and where "every atom counts" [51,52], is required in order to rationalize their catalytic activity and to form a base for future experimental investigations. To the best of our knowledge, detailed, systematic studies of MgO-supported sub-nanometre AuCu clusters have not been reported, despite many publications on the structural and catalytic properties of larger free and MgO-supported AuCu nanoparticles [8,50,[53][54][55]. Theoretically, sub-nanometre sizes present a synergistic combination between employing high level theory (e.g.…”
Section: Introductionmentioning
confidence: 99%